Comparative strategies for stem cell biodistribution in a preclinical study - Wang Fang; Wang Zhe; Wang Fen; Dong Kelly; Zhang Jing; Sun Yun-juan; Liu Chun-feng; Xing Mei-jie; Cheng Xue; Wei Su; Zheng Jia-wei; Zhao Xiong-fei; et al. (Acta Pharmacologica Sinica, 2020)
Stem cell therapy represents the potential alternative effective strategy for some diseases that lack effective treatment currently. Correspondingly, it is crucial to establish high-sensitive and reliable quantiﬁcation assay for tracing exogenous cell migration. In the present study, we ﬁrst used both bioluminescence imaging (BLI) indirect labeling (human norepinephrine transporter-luciferase reporter system) and 89zirconium (89Zr)-hNSCs direct labeling combined with positron emission tomography/computer tomography (PET/CT) system for tracking human neural stem cells (hNSCs) migration into the brain via nasal administration in preclinical study. But the above two methods failed to give the biodistribution proﬁle due to their low sensitivity. Considering its superior sensitivity and absolute quantitation capability, we developed and validated the droplet digital PCR (ddPCR) targeting species-speciﬁc gene in frozen and parafﬁn sections, slices, and whole blood with the sensitivity of 100–200 hNSCs. Accurate and high throughput quantiﬁcation could be performed using ddPCR with the coefﬁcient of variation (CVs) of lower quality control (LQC) below 30%. In combination with immunohistochemistry and ddPCR, we conﬁrmed the migration of hNSCs into the brain via nasal administration, which supported the efﬁcacy of hNSCs in MPTP-treated mice, an animal model of Parkinson’s disease. In conclusion, the present study is the ﬁrst to report the application of ddPCR in the pharmacokinetics proﬁle description of tracking of hNSCs in preclinical studies.